Impact of Marketing Activities on the Image of an Energy Company: A Case Study of Electricity Suppliers in Poland - DĄBROWSKI, Jakub; GOŁĄB-ANDRZEJAK, Edyta (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025DO - 10.14505/jemt.v16.3(79).04, 2025)
In the energy sector, building a positive image has gained particular importance due to rising energy prices and the ongoing transformation. Companies in this sector now focus on operating with respect for the natural environment. Their activities align with the concepts of sustainable development, ensuring the security of electricity supply, and providing consumers with freedom of choice in goods and services. In the strategic document “Poland’s Energy Policy until 2040”, it is assumed that by 2040, zero-emission sources will account for more than half of the installed capacity. At the same time, decentralized and citizen-driven energy production, based on local capital, will continue to develop. This means that energy companies will compete for the prosumer market, which consists of individuals generating energy from small-scale renewable energy installations at home. From the perspective of an energy company, image creation therefore plays a crucial role in building market position and achieving a competitive advantage. Managing marketing activities to establish a positive image is therefore one of the key elements of the marketing management process within the company. There is a clear need for research and analysis in the field of marketing activities in the energy sector, as there is still a lack of publications dedicated to this topic. Moreover, the ongoing energy transition in Europe, aimed at achieving climate neutrality by 2050, presents energy companies with the significant challenge of shaping their image in alignment with the vision of the “European Green Deal”. Therefore, the objective of this article is to determine how marketing activities undertaken by electricity suppliers influence their image. Referring to the resource-based view (RBV) of the firm and signaling theory, research hypotheses were formulated, and a model was developed, assuming a positive impact of selected marketing activities on a company’s image. To achieve the study’s objective, a quantitative survey was conducted using the Paper-and-Pencil Interview method among a randomly selected sample of 503 electricity consumers. The collected data were subjected to statistical analysis. The results show that marketing activities undertaken by electricity suppliers, such as offering energy products bundled with energy (packages), offering discounts, providing an online customer service platform, operating a physical customer service office and engaging in sponsorship activities, have a positive impact on their image. This study is one of the first empirical investigations into the relationship between specific marketing activities and the corporate image of electricity suppliers in Poland. By integrating the resource-based view and signaling theory in the context of the energy sector's transformation, it offers a novel conceptual and methodological approach to evaluating image-building efforts in a highly regulated and evolving market. This study has three main limitations. Focuses on selected elements of the marketing mix, omitting other potential factors that can influence the corporate image. Data were collected from household consumers, which can limit the depth of insight into perceptions of marketing activities. This study was carried out within the Polish energy market; therefore, it should not be assumed that the findings will apply to electricity providers operating in other countries or under different regulatory conditions.